IMPLEMENTASI PERENCANAAN KAS SEBAGAI UPAYA UNTUK MENCIPTAKAN REALISASI ANGGARAN YANG PROPORSIONAL PADA KANTOR PELAYANANAN PERBENDAHARAAN NEGARA SAMARINDA TAHUN ANGGARAN 2011 - Eriyandi, Vina (EKONOMIA, 2012)
Cash planning is a list of funding needs prepared by the office and submitted to the State of Treasury Office for a specific period in the implementation of the State Budget. Cash planning implemented to create a proportionate realization. Implementation of cash planning at State of Treasury Office of Samarinda generating a disproportionate realization. This is due to high deviation between the planned and realized.